ანტიკური ჰადესის რეცეფცია ქართულ ლიტერატურაში - კობახიძე, ეკატერინე (ლოგოსი, 2020)
The contemporary studies of the classical tradition in the Georgian literature threw more light upon the viewpoint that elements of antiquity might be present at every developmental stage of Georgian literature. We can say with some confidence that the Greek-Roman components and their interpretations are confirmed at the substrate layers of the European Literature, however, the question as to how organic representations of antiquity are for the Georgian literature has not yet become an object of scientific study. The research into this important question will shed the light upon many significant points of interest, of which the most important consists in the problem of identity of the Georgian literature. The issue how important the element of antiquity is for the Georgian literature, of course, deserves a large scale of systemic study; however, some generalizations could be made by observing different spheres, perceptions on mythological plots or groups of plots. For this purpose, the mythological narrative and terms have been selected, which are linked with the Greek-Roman representations of one of the oldest and most complex sphere – the kingdom of the dead–Hades. It is noteworthy, that the interest for the fictional images of the antique Hades in the World, and especially in the European literature has been characteristic since the early developmental stages. Consider for example, Dante’s the “Divine Comedy”, which alongside Virgil’s the “Aeneid” provides for the traces of the antique Hades in “Inferno”. It should be noted that the earliest reflections on this thematic group in the Georgian literature appeared in XII-XIII centuries. The unknown author of the „Life of Kartli”, in his work “The Life of King of Kings Giorgi” and the poetic work “Tamariani” by Chakhrukhadze confirms the abovementioned supposition with concrete examples. The article provides for the more or less complete picture of the mythological narratives and terms linked with antique ideas concerning the future world reflected at all stages of development in the Georgian Literature. The provided terms include: Pluto, Persephone, Hades, Charon, Acheron, Lethe, Elysian Fields, Styx, Cerberus etc. The study analyzes more than 40 different quotations from different authors of different eras and their respective works, alongside the terms which together with accompanying scientific commentaries provides the full picture of its reflection in the Georgian literature. Studying the aforementioned questions in this way, allows observing the interesting process of literary interpretation and transformation of the terms, which itself is important for drawing generalized conclusions. It is noteworthy, that links with some of the terms related with the Antique Hades is confirmed at all the literary stages, while some of the characters are visible only in a given time span, mainly, in the contemporary literature. To explain this observation several assumptions are being developed in the article. Considering the general context, the usage of those mythological terms can be broadly grouped in two clusters, namely: 1. Antique mythological figures which are included in the relevant mythological narrative; 2 antique characters included in a completely new, original narrative/context. In addition, some important examples of perceptions on antiquity, which provide for interesting and original examples of reflection of the classical tradition, deserve to be studied as the separate issues. Finally, based on the analysis of the provided material, conclusions are provided concerning how organically these elements are placed into the traditional Georgian literary images base, and the issue of their significance in the history of the Georgian literary writing.